Ideological resistance to veg*n advocacy: An identity-based motivational account - De Groeve, Ben; Bleys, Brent; Hudders, Liselot (Frontiers in Psychology, 2022)
Animal-based diets in Wwestern countries are increasingly regarded as unsustainable forbecause of their impact on compromising public human health, environmental and animal welfare. Promoting shifts toward more plant-based diets seems an effective way to avoid these harms in practice. Nevertheless, calls claims against animalthe consumption of animal products-based diets contradict the ideology of the omnivorous majority known as carnism. (known as “carnism”) which Carnism supportslegitimizes animal-product animal-product consumption consumption as a cherished social habit that is harmless and unavoidable and delegitimizes invalidates minorities with plant-based dietsdietary minorities: vegetarians and vegans (veg*ns). In this articletheoretical review, we integrate previous socio-psychological and empirical theorizing literature and to provide an identity-based motivational account to understandof ideological resistance against veg*ns and plant-based food advocacy. We argue that aAdvocates who claim argue against that animal-based dietsthe consumption of animal products often make claims that it is are harmful, and avoidable by making dietary changesadopting toward veg*n dietsplant-based diets. In response, omnivores are likely to evoke experience a simultaneous threat to omnivores’ their moral identity and self and/or group interests attached to their identity as consumer of animal products, which may arouse . This may (carnist identity), arouseing identity-based motivations to rationalize animal-based dietsthe consumption of animal products and to obscure harms. . SuchIf omnivores engage in such motivated reasoning and ignorance, this may also inform negative negative stereotyping and stigmatization of plant-based veg*n advocates. These “pro-carnist” and “counter-veg*n” defenses can be linked with various personal and social motivations to eat animal products (e.g., meat attachment, gender, speciesism) and reinforce commitment to and ambivalence about eating animal products., which allows to avoid informational influence. This does not necessarily mean, however, that plant-based veg*n advocates cannot exert any influence. An initial apparent resistance may mask delayed conversion and private acceptanceindirect and private acceptance of advocates’ claims of the advocate’s message, priming commitment to change behavior towards more plant-basedveg*n diets often at a later point in time. Based on our theoretical account, We discuss limitations of our framework and we provide directions for future research.